Eccrine angiomatous hamartoma: Late onset facial presentation - Chinmay Halder; Biswanath Naskar; Projna Biswas; Pradip K Mitra (Wolters Kluwer Medknow Publications, 2014)
Eccrine angiomatous hamartoma (EAH) is a very rare benign neoplastic condition characterized by hamartomatous proliferation of eccrine glands and accompanying blood vessels and lymphatics. These lesions are more often present at birth or appear during early infancy and childhood and present as solitary nodule or plaque with occasional pain and sweating. They are generally present on the extremities, mostly the palms and soles. We report here a case of EAH in a 20-year-old female who presented with a solitary angiomatous plaque close to the lower eyelid of the right eye with occasional pain and sweating for its rarity.